Roman law, Scots law and legal history selected essays - Gordon, William M. (Edinburgh : Edinburgh University Press, 2007)
This collection draws together much of William M. Gordon's most important writing and, as such, will be an indispensable purchase for all those interested in these core areas of legal scholarship.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Law -- Scotland; Roman law; Law -- History; Roman law -- Influence; Law